K. Schoeman, Early Slavery at the Cape of Good Hope, 1652-1717: Great on Detail but Lacking in Historiography (Historia, 2021)
In this book, Karel Schoeman has provided a richly detailed account of slaves and slavery at the Cape during the early years of the Vereenigde Oost-Indische Compagnie (VOC) or the Dutch East India Company. Schoeman's approach to the subject has been to read widely in the secondary sources, and in those primary sources which have been published, to produce a narrative that is partly chronological and partly thematic. It is an impressive and valuable contribution to Cape slave studies that contains a great detail of information about the conditions under which slaves worked, as well as revealing glimpses of individual slave lives. Where possible, Schoeman has presented details concerning the origin of Cape slaves. He has also attempted to gauge their numbers and their dates of arrival at the colony. With the help of the index, historians of Cape slavery will now be able to find answers to a great many questions which might interest them. If one wants to know, for instance, what slaves wore, how they were housed or what they ate in the early eighteenth century, Schoeman's text provides many examples. As a synthesis of existing knowledge, it is invaluable. Despite its length, however, it is not complete.